Cognitive poetics : goals, gains and gaps - Brône, Geert, 1978-; Vandaele, Jeroen (Berlin ; New York : Mouton de Gruyter, 2009)
For more than two decades now, cognitive science has been making overtures to literature and literary studies. Only recently, however, cognitive linguistics and poetics seem to be moving towards a more serious and reciprocal type of interdisciplinarity. In coupling cognitive linguistics and poetics, cognitive poeticians aim to offer cognitive readings of literary texts and formulate specific hypotheses concerning the relationship between aesthetic meaning effects and patterns in the cognitive construal and processing of literary texts. One of the basic assumptions of the endeavour is that some.
Frontmatter -- Table of contents -- Cognitive poetics. A critical introduction -- Part I: Story -- Text worlds -- Cognitive approaches to narrative analysis -- Reflections on a cognitive stylistic approach to characterisation -- Part II: Figure -- Minding: feeling, form, and meaning in the creation of poetic iconicity -- Metaphor and figure-ground relationship: comparisons from poetry, music, and the visual arts -- Part III: Stance -- Deconstructing verbal humour with Construction Grammar -- Judging distances: mental spaces, distance, and viewpoint in literary discourse -- Does an "ironic situation" favor an ironic interpretation? -- Part IV: Critique -- How cognitive is cognitive poetics? The interaction between symbolic and embodied cognition -- Epilogue. How (not) to advance toward the narrative mind -- Backmatter.
Includes bibliographical references and index.
Print version record.
In English.
eBooks on EBSCOhost
Keywords: Cognitive grammar; Poetics; Literature -- Philosophy; Grammaire cognitive; Poétique.; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax; Literature -- Philosophy; Cognitive grammar; Poetics; Cognitive linguistics; textlinguistics; Electronic book